Relationship between acoustic wave velocity and mechanical properties in Acacia mangium wood - Van Duong, Doan; Hasegawa, Masumi (Maderas. Ciencia y Tecnología, 2024)
There is a strong interest in developing and using acoustic technology to evaluate the mechanical properties of wood in situations where a static bending test is not feasible to undertake. In this study, the mechanical properties of Acacia mangium (black wattle) wood were predicted by using stress wave and ultrasonic wave methods. The values of dynamic modulus of elasticity based on stress wave and ultrasonic wave were 9,29 % and 4,75 % higher than those obtained from static modulus of elasticity, respectively. There was no statistically significant correlation between acoustic velocity and mechanical properties measured by destructive tests. The strong experimental correlation coefficients were found between stress wave and modulus of elasticity (r = 0,94; P < 0,001), and ultrasonic wave and modulus of elasticity (r = 0,83; P < 0,001). This result indicates that stress wave and ultrasonic wave techniques are suitable for predicting the static modulus of elasticity of Acacia mangium (black wattle) wood if the density of the measured elements is known. There was no dependence of wood density and acoustic propagation velocity measured in this study, whereas statistically significant correlations were found between the fiber length with stress wave velocity (r = 0,44; P < 0,05) and ultrasonic velocity (r = 0,48; P < 0,05).